Evaluation of herbicidal potential of commercial herbicides in wheat (Triticum aestivum L.) cultivation - Awni Abdalbaki, Hussein Ali Khalid, Hussein Ali Salim, Abdalsalam; Salam Farhan Dawood, Abd Alrasool Shalal Taha (Recent Research in Science and Technology, 2017)
A field experiment was conducted in Kanan region, province of Diyala, Iraq during the winter season 2016-2017 to screen herbicides for wheat cultivation. Six herbicides viz., Salix, Cronus, Pallas, Granstar, Topic and Atlantis were sprayed as post-emergence with second irrigation 54 days after crop sowing. Wheat growth parameters viz Crop height, Spike length and number of grains per spike were a higher in Granstar&Topic (105.2 cm, 12.6 cm, 51.4) respectively, 1000 grain weight were noted with Atlantis (40.9 g). followed by Granstar&Topic (39.2 g), Number of plants / m2 was a higher in Atlantis (430), Grain yield g \ acre was significantly increased in Granstar&Topic (1848 g) weeds growth parameters like Number of weeds / m2, Dry weight of weeds g, Weed control % and Weeds inhibition % were lower in Salix&cronos (0.0,0.0 g,100%,100%) respectively.